Penerapan Problem Based Learning Berbasis Kearifan Lokal Simalungun dalam Meningkatkan Keterampilan Sosial dan Kesadaran Budaya Siswa SMP Negeri 2 Silimakuta - Sembiring, Faulina Br; Haloho, Bongguk; Purba, Corry (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Educational issues in Indonesia reflect complex challenges, ranging from low teaching quality to limited infrastructure and a lack of innovation in learning models. This study aims to explore the effectiveness of a Problem Based Learning (PBL) model based on Simalungun local wisdom in enhancing students’ social skills and cultural awareness in Integrated Social Studies. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The research was conducted at SMP Negeri 2 Silimakuta, involving teachers and eighth-grade students engaged in project-based learning. The findings indicate that the implementation of PBL increased students' active participation, critical thinking, and social skills such as collaboration and communication. Furthermore, students demonstrated improved cultural knowledge, greater appreciation for local heritage, and a stronger commitment to preserving Simalungun culture. The PBL model based on local wisdom effectively connects academic learning with real-life contexts, fostering student character development that is adaptive and socially and culturally aware. These results underscore the importance of integrating local values into learning strategies as a contextual approach to education in Indonesia.